2000
DOI: 10.1042/bj3520211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by glucagon (cAMP) and insulin of the promoter of the human phosphoenolpyruvate carboxykinase gene (cytosolic) in cultured rat hepatocytes and in human hepatoblastoma cells

Abstract: A promoter fragment (-457 to +65) of the human cytosolic phosphoenolpyruvate carboxykinase gene, which by analogy to the rat promoter contains regulatory regions conferring glucagon (cAMP) and insulin responsiveness to the phosphoenolpyruvate carboxykinase gene, was cloned into a luciferase expression vector and transfected into cultured rat hepatocytes and human hepatoblastoma cells (HepG2) to study the regulation of the transgene by glucagon (cAMP) and insulin. A reporter gene that contained the rat promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“…2, there is some E-box like elements in the proximal promoter of the human glucagon receptor. Although others have shown HepG2 cells to be glucose responsive (Carriere et al, 2005;Elsas et al, 2002), in our hands this cell line was non-responsive to glucose when tested with a PEPCK promoter construct previously shown to be glucose responsive in primary hepatocytes (Cournarie et al, 1999;Rucktaschel et al, 2000) (data not shown). Thus, we were unable to examine the glucose regulation of the human glucagon receptor promoters in the HepG2 cells.…”
Section: Discussioncontrasting
confidence: 67%
“…2, there is some E-box like elements in the proximal promoter of the human glucagon receptor. Although others have shown HepG2 cells to be glucose responsive (Carriere et al, 2005;Elsas et al, 2002), in our hands this cell line was non-responsive to glucose when tested with a PEPCK promoter construct previously shown to be glucose responsive in primary hepatocytes (Cournarie et al, 1999;Rucktaschel et al, 2000) (data not shown). Thus, we were unable to examine the glucose regulation of the human glucagon receptor promoters in the HepG2 cells.…”
Section: Discussioncontrasting
confidence: 67%